Selective screening imaging of the aortoiliac arterial system in kidney transplant candidates with non‐contrast pelvic computed tomography. Issue 7 (12th May 2021) - Onaca, Nicholas; Martinez, Eric; Bayer, Johanna; Wall, Anji; Fernandez, Hoylan; Ruiz, Richard; Ma, Tsung‐wei; Gupta, Amar; McKenna, Gregory; Testa, Giuliano
Abstract: Non‐contrast pelvic computed tomography (CT) can detect severe iliac artery calcifications that present technical contraindications to kidney transplantation (TCT). We screened 454 asymptomatic patients with a history of any of the following: hemodialysis >10 years, diabetes mellitus >20 years, coronary artery disease (CAD) with percutaneous or surgical interventions, carotid disease, diabetes with below‐/above‐knee amputations, and heart‐kidney transplantation candidacy. Patients with normal dorsalis pedis and/or tibialis posterior pulses were not screened. A total of 8.4% had severe calcifications with TCT; CT determined laterality for implantation in 13.9%. No patients with the following characteristics were classified as TCT: age <40 years, hemodialysis >10 years, carotid arterial disease, prior lower extremity amputation, or heart‐kidney transplantation candidacy. CAD was associated with TCT in univariate though not multivariate analysis. Limiting screening to patients >40 years, with DM >20 years, or with CAD, 9.8% had a TCT and CT determined transplant laterality in 14.2%. Screening for severe iliac artery calcifications is useful for selected kidney transplantation candidates over age 40. It can assist with laterality choice or surgeon determination of TCT. Cost and radiation exposure risks should be weighed against the morbidity risks from unnecessary surgery.